Measles second dose vaccination coverage and associated factors in Ethiopia: A systematic review and meta-analysis - Aklilu Alemayehu; Sisay Tefera (Vaccine: X)
Background: Measles-containing vaccine second dose (MCV2) is an important intervention employed to eliminate measles that mainly affect children. Although there are few original studies, comprehensive data that can guide evidence-based decision making to mitigate measles in Ethiopia is limited. Thus, this systematic review and meta-analysis aimed to synthesize evidence to fill this gap. Methods: Online searching, selection, data extraction, and quality assessment were conducted by two authors. Data were extracted using Microsoft Excel Spreadsheet Version 19.0 and analyzed using STATA Version 17.0. Pooled estimates were determined by a random-effect meta-analysis. Sub-group analysis was conducted to account for sources of heterogeneity. Results are presented in narration, tables, and figures. Results: Eight cross-sectional studies involving 4416 participants from four regions of Ethiopia were included in this SRMA. The pooled coverage of MCV2 vaccination in Ethiopia was 50.5 % [95 % confidence interval (CI): 39.0–61.9]. Maternal education [odds ratio (OR) = 2.14 95 % CI: 1.22–3.05)], child delivery in a health facility (OR = 2.16 95 % CI: 1.30–3.02), having knowledge about child immunization (OR = 2.24 95 % CI: 1.61–2.87), favorable attitude towards child immunization (OR = 4.30 95 % CI: 2.63–5.97), having awareness about MCV2 vaccination (OR = 2.04 95 % CI: 1.48–2.59), having postnatal follow-up (OR = 2.52 95 % CI: 1.39–3.65), and utilization of other vaccines and supplements (OR = 4.17 95 % CI: 2.05–6.28) were factors associated with MCV2 vaccination coverage. Conclusion: The coverage of MCV2 vaccination in Ethiopia is sub-optimal. The identified factors should be targeted to improve MCV2 vaccination coverage, and hence strengthen measles mitigation.